The Ḥudūdnāme Concerning the Borders of the Bosnian Villayet With Austria After the Peace of Karlovci (Prilozi za orijentalnu filologiju, 2017)
The question of the borders of the Bosnian Pashalik, drawn on the basis of the decisions of the peace treaty concluded in Sremslki Karlovci in 1699, has not been treated so far in Yugoslav historiography, although it represents an important question in the history of Yugoslav peoples, and especially in the history of the peoples of Bosnia and Herzegovina. Under the provisions of this treaty, signed by the members of the Holy Alliance on the one hand, and the Ottoman Empire on the other, the Bosnian Pashalik obtained its first permanent and fixed borders on the north, west, and southwest.A critical edition of the text of the treaty regarding the borders of the Bosnian Pashalik with Austria (hereafter referred to as the ḥudūdnāme) has been prepared on the basis of four manuscripts of the ḥudūdnāme in Turkish. Two copies of the ḥudūdnāme are kept at the Archives Museum of Topkapi in Istanbul. The text of what is thought to be the better manuscript is published here; the other copy is designated by the abbreviation TMA. Both are found in the same codex the call number of which, in translation, reads: Defter No. 7014 -- 14 dhu'l-qa'da, 1112 (23 April 1701). Later the call number has been changed and now reads: 7015. The third copy of the ḥudūdnāme, the one abbreviated as NB, is kept at the National Library in Sarajevo; but, since it has not been processed yet, it does not have a call number of its own. The fourth copy, designated by the abbreviation S, is in the possession of the family of the late Dr. H. Šabanović.A literal translation of this document makes it possible for us to trace distinctly the border of the Bosnian Pashalik along its complete length. According to the ḥudūdnāme, the border ran as follows: from the conflux of the Bosut and the Sava up to the mouth of the Una, the border was the Sava River; from there it was the Una River up to the mouth of the creek Divuša, where the border crosses over to the left bank of the Una and goes between Bužim and Gvozdanski, reaching the Glinica River which marks the border until it flows into the Glina, from whence the border is formed by the Glina River up to the place where the creek Rabinja empties into it. The border between the two countries is further constituted by the creek Rabinja all the way up to its source in the region of Gornja Glina. The borderline from there comes out on the creek Grabovac, continues along the creek Krnjeduša, emerging at the creek Gnojnica, goes on to the Korana, crosses to the left bank of the Korana, climbs the hill above Furjan, leaving the ruins of the town of Furjan on Turkish territory. From here, the border further passes by the source of the Furjašnica, continues along the foothills of the Mašvina Mountain, goes up to the top of the Bliznica Mountain, goes down into the Rakovac Field, and, in a more or less straight line, crosses the Korana again near the Mlinski prelaz (pass) in the vicinity of the village of Catrnja, then reaches Pogledalci Hill, from where, continuously following the mountain ridges, it comes to the summit of Plješivica, proceeds to Kuk Peak and then across the Mazinska Mountain, Cemernica and Stražbenica near Srb it passes through the Srb Gorge, reaches the Poštak Mountain, descends into the Vilin Gorge, passes over the Žujino Field, comes up to Bilo Hill, then to Otonsko Crest and ends at the junction of three borders - on Debelo Hill, nortwest of Knin.A relatively small number of unidentified toponyms mentioned in the ḥudūdnāme represent, in essence, less significant, secondary localities which cannot be found even in the best regional geographic maps of the area through which the borderline passes nor are they in use among the local people.